Environment and natural resource conservation and management in Mozambique - Mawere, Munyaradzi (Langaa Research & Publishing CIG, 2013)
This is a narrative of the environmental and natural resource conservation and management issues in Mozambique. While the topics in this volume are diverse, they are all explicitly designed to move beyond the routinized blame of natural resource mismanagement and environmental degradation on local communities, and to rethink ecosystem destruction, land degradation, and natural resource over-exploitation in Africa and beyond. Never losing sight of the major causes of environment and resource mismanagement in Mozambique, the book advances the thesis that environment and resource problems are a result of compound factors such as poor governance, poverty, corruption, low education levels, and disregard of endogenous conservation epistemologies. A combination of all these factors makes the terrain of conservation even more complicated than ever; hence the need for urgent action by all social actors.